Program minim gadget anak cerdas (MGAC) Kelurahan Pondok Cina - Nuraeni, Aisyah; Latifa, Alma Yulia; Ilma, Hafizha; Fitriani, Ishlah; Aurellia, Monica (Journal of Youth and Outdoor Activities, 2024)
Background: Pondok Cina Village is one of the areas of Depok City, West Java Province. This village is part of the Beji District, Depok. Administratively, each area is bordered by various roads. Findings: The cleanliness of garbage and gutters is good and residents are aware not to litter. Regarding waste disposal and management, residents are assisted by cleaning staff. However, there are still residents who burn and bury garbage. Recently, a communal toilet was built, which was previously intended for several houses but has now been built, so that one house already has its own toilet. Methods: The type of research used in this study is descriptive qualitative research which is used to describe a phenomenon or symptom. Conclusion: After the community understands that the behavior of early childhood children who often throw tantrums when their wishes to use gadgets are not fulfilled is a problem, in the future they will automatically reduce the intensity of giving gadgets to early childhood children. The purpose of this project is to build public awareness of the importance of providing a parenting pattern in which good communication and interaction between parents and children is established to support child development. This project will involve target groups to be proactive in solving problems. Therefore, this program tries to empower a number of stakeholders to create independence for the Pondok Cina Village community in dealing with quality of life problems.